HUBUNGAN KEHADIRAN KELUARGA DENGAN TINGKAT KECEMASAN PERAWAT SAAT RESUSITASI DI RUMAH SAKIT BANJARMASIN - Atika Luqyana; Julianto Julianto (LPPM Universitas Sari Mulia, 2020)
Background: A life-saving medical action can cause anxiety, due to threats to body integrity, emergency response actions always prioritize patient safety, where the presence of the patient's family who sees the nurse's actions when resuscitating the nurse must act quickly and eventually feel anxious due to the anticipation of errors. Objective: This study aims to determine the relationship between the level of anxiety of nurses when performing resuscitation with the presence of family next to the patient. Methods: This study used a cross sectional design. The population was all nurses in the ICU with a sample taken with a total sampling technique of 30 people. Data analysis using rank spearman. Results: The results showed that most nurses experienced mild anxiety. Conclusion: There is a family relationship with the anxiety level of nurses during resuscitation in the ICU room at RSUD Dr. H. Moch Ansari Saleh Banjarmasin with moderate relationship strength.